Urgensi Penerapan Prinsip Keselamatan dan Kesehatan Kerja (K3) Terhadap Pekerja Pengelola Limbah Industri CV Hijau Alam Kecamatan Bukit Bestari Kota Tanjungpinang - Dyas Puzi Rahmadina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In Indonesia Occupational Safety and Health (K3) is often ignored, this can be seen from the many cases in companies that experience work accidents and other Occupational Safety and Health (K3) problems because companies pay little attention to K3 aspects and neglect to apply the principles of Occupational Safety and Health (K3) according to the standard. To find out whether the CV. Green Nature has/has not applied the principles of occupational safety and health (K3) to industrial waste management workers. This type of research is descriptive qualitative with data collection techniques in the form of observation, interviews, and literature study. Shows that CV.Hijau Alam has not optimally applied the principles of occupational safety and health (K3). implementation is constrained due to low awareness of the importance of OSH.